Estrategia de marketing en la librería y papelería Continental - Gordillo Veliz, Nadia Silvana (2020)
The subject of this work focuses on Marketing strategies for the Continental bookstore and stationery, a micro-business created a little over 20 years ago, and which is located in the center of the city of Ventanas. In this sense, it presents as a general objective the "Determine marketing strategies to increase sales and improve the competitiveness of the bookstore as well, it is framed that Qualitative and quantitative research was carried out, being used as a method for collecting information, for this it was It is necessary to apply interviews and surveys to the inhabitants of the city of Ventanas as well as to the members of the company. The analysis of the surveys allows to know how the behavior of the clients is at the time of making the purchase, where said company must take preventive measures to satisfy the market niche. After the investigation, it was determined that this company did not have a sales strategy or websites that would inform the community about products, promotions, payment methods, etc. That is why we suggest the implementation of functional marketing strategies that deal with the 4p's that are: price, product, place and promotion, with special emphasis on price attention to retain customers by helping to position themselves in the market.